Pendampingan Pengelolaan E-Commerce Mitrapurwo.Id untuk Optimalisasi Marketing Produk Usaha Mikro Kecil dan Menengah Desa Purwojati - Wahyuningtyas, Neni; Adi, Khofifatu Rohmah; Idris; Rosyidah, Yuniar (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2024)
Mitrapurwo.id's e-commerce management assistance program is designed as a solution for optimizing the marketing of superior UMKM products in Purwojati Village in Mojokerto Regency. This is a response to the challenges faced by UMKM in the midst of the COVID-19 pandemic and unstable global economic conditions. Mitrapurwo.id e-commerce is a platform developed by Abdimas Team from Universitas Negeri Malang since 2022 to help market Purwojati Village UMKM products. However, UMKM still faces obstacles in operating this platform due to a lack of digital literacy and knowledge about online business management. To overcome this problem, the Universitas Negeri Malang collaborated with the Purwojati Village Government to organize a mentoring program. This program includes six stages, including business analysis, increasing knowledge and skills, and optimizing the use of mitrapurwo.id e-Commerce. The evaluation results show a significant increase in business management knowledge and skills as well as the use of technology, especially e-commerce mitrapurwo.id. All program participants successfully applied the knowledge gained in their businesses. This program is also considered successful in helping develop product innovation, business growth and marketing of Purwojati Village UMKM products. This mentoring program has succeeded in providing broad benefits for Purwojati Village MSMEs by increasing knowledge, skills and utilization of mitrapurwo.id e-commerce. This program also has the potential to be further developed with innovative features in the mitrapurwo.id e-commerce platform to support the growth of Purwojati Village UMKM businesses and increase the involvement of the general public.